Image fusion using FPGA in multi-sensor optoelectronic systems - Nguyen Quang, Dr Hiep; Tran Dinh Hoa; Dang Van Tang (Journal of Military Science and Technology, 2025)
This study proposes a foundation for developing a real-time image fusion system for multi-sensor optoelectronic systems applied in defense and security, aiming to enhance target detection by combining images from thermal imaging and low-light channels. The VIP Board Big V3.8 with Cyclone IV FPGA, a custom FPGA development board, which integrates key peripherals such as SDRAM, VGA, HDMI, and image sensors, is utilized. The main hardware modules have been designed, including global clock management (PLL), UART communication, FIFO buffers, LCD display control, and image fusion. The image fusion module employs an algorithm that decomposes images into two layers, the base layer and the detail layer, enabling efficient data fusion from two input images to generate a high-quality output image. Experimental results demonstrate that the system operates stably, meeting speed and low-latency requirements, paving the way for future research on more powerful FPGA platforms.